Shall we kill again? Violence and intimacy among the “awajun “new leaders” in the northeastern Peruvian frontier - Silvia Romio (Íconos)
In societies living at the margins of the State, interpersonal relationships and the use of power, as well as competition dynamics, are often similar among different groups in spite of preexisting differences in access to economic resources, moral authority and personal prestige. From this point of departure the present article undertakes an ethno historic analysis which attempts to illuminate changes affecting the Alto Marañon (Peru) Awajun people, between the years 1950 and 1970. The socio-cultural transformation this indigenous group was forced to undergo in order to attain membership in the wider national society, is described. Using the tools which ethno history and the anthropology of affectivity provide, and paying particular attention to the topic of the building of the “heroic body”, the present text focuses on how Awajun society suffered significant changes regarding the of the use of force and of the symbolic management of violence, leading to the assimilation of new styles of indigenous leadership. All this occurs as a result of experiences resulting from close contact with the earliest agents of government authority to show up in their native homelands: evangelical missionaries and the army. This process led the Awajun to the development of unprecedented forms of “indigenous leadership”, resulting from the assimilation, convergence and reworking of cultural material incorporated during their contacts with religious and military personnel.